Purification and lipid-layer crystallization of yeast RNA polymerase II. - Edwards, A M (1990)
Yeast RNA polymerase II was purified to homogeneity by a rapid procedure involving immunoaffinity chromatography. The purified enzyme contained 10 subunits, as reported for conventional preparations, but with no detectable proteolysis of the largest subunit. In assays of initiation of transcription at the yeast CYC1 promoter, the enzyme complemented the deficiency of an extract from a strain that produces a temperature-sensitive polymerase II. Mammalian RNA polymerase II was inactive in this initiation assay. The purified yeast enzyme formed two-dimensional crystals on positively charged lipid layers, as previously found for Escherichia coli RNA polymerase holoenzyme. Image analysis of electron micrographs of crystals in negative stain, which diffracted to about 30-A resolution, showed protein densities of dimensions consistent with those of single polymerase molecules.